Information and Communication Technology to Facilitate Learning for Students in the Health Professions: Current Uses, Gaps and Future Directions - Ellen Costello; Mary Corcoran; Jacqueline Barnett; Marisa Birkmeier; Rhea Cohn; Ozgur Ekmekci; Nancy Falk; Thomas Harrod; Debra Herrmann; Sean Robinson; Bryan Walker (Online Learning, 2014)
Changes in the US Healthcare System along with the need for institutions of higher education to prepare a work force ready to address the challenges of today and tomorrow have highlighted the need to incorporate technology in its broadest sense as part of the student learning experience. In health professional education, this becomes challenging as programs have traditionally relied on face-to-face instruction along with internship experiences which provide hands on patient care. In addition, learning activities that incorporate higher order critical thinking must be incorporated in order to meet competency based professional expectations as well as expectations in the work place environment. This article will address current technology use in health professional education programs and identify opportunities to incorporate technology to enhance the student learning experiences with emphasis on the critical thinking, communication, and psychomotor skills required of today’s health professional graduate.